Lichens of the Prince Olav Coast, Antarctica - カシワダニ, ヒロユキ; KASHIWADANI, Hiroyuki (1970)
P(論文) 1. Seventeen species of lichens were recognized among the collections from the Prince Olav Coast. Of these lichens, 15 species are new to the flora of the Prince Olav Coast. 2. The 17 species studied include thirteen crustose, two fruticose, and two foliose lichens. 3. Crustose lichens were mostly fertile and both fruticose and foliose ones were thoroughly sterile. 4. The exposed areas of the continent are rich in lichen flora, while only a few lichens can be found on the Ongul Islands. departmental bulletin paper